A review of fatigue performance of bolted connections in offshore wind turbines - Lochan, Sharda; Mehmanparast, Ali; Wintle, John (Elsevier, 2019)
Flanged bolted connections are used in offshore wind turbines to connect the monopile to the transition piece, and the transition piece to the tower. Forces and moments generated by the effects of winds, waves and currents subject these connections to variable amplitude cyclic loads. In the harsh marine offshore environment areas such as bolt threads are vulnerable to fatigue cracking and failure. Their structural integrity and life are influenced by coatings, lubricants, bolt size, design and tension, manufacturing tolerances and flange contact. This paper presents a review of the main challenges for fatigue life assessment of M72 bolted connections used in offshore wind turbines to connect the monopile to the transition piece, and the factors affecting the fatigue performance. Existing standards and guidelines along with different fatigue assessment methods presented in the literature are discussed in terms of their suitability for fatigue life assessment of M72 bolted connections for offshore wind turbines. One of the key challenges in fatigue life assessment of large scale bolts (e.g. M72) is the lack of experimental data points from which fatigue design curves can be derived. Recommendations are made for how to improve the current best practice for fatigue assessment of large scale bolted connections in the offshore wind industry and potential areas for further investigation are proposed for future research.
Keywords: bolted connection; preload; fatigue; transition piece